Self-regulated Learning in Secondary Level English Textbooks in China - Zou, Fengmei (Journal of Tikapur Multiple Campus, 2023)
This paper explores the place of self-regulated learning in English language curriculum in China with a special focus on the analysis of English textbooks prescribed for secondary schools in Guangdong. Four textbooks prescribed for two semesters of grades 7 and 8 each, and curriculum of the same level were analyzed to explore to what extent the self-regulated learning has been adopted in the curriculum and textbooks. The findings reveal that both curriculum and textbooks promote self-regulation, which supports to achieve the curricular goals of learning a language. The implications are that such an exclusive focus on self-regulatory processes in the textbooks has a high potential to realize the goal of promoting self-initiated and independent learning in China’s secondary education.